Pengembangan Model Pembelajaran Kolaboratif Antara Guru dan Orang Tua dalam Mendukung Kemajuan Belajar Siswa di Sekolah Dasar - Mutiara Sabrina; Mutia Hairani; Syahrial Syahrial (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
The objective of this study is to explore the evolution of a collaborative learning framework involving educators and parents, aimed at enhancing student academic progress in elementary educational settings. A variety of scholarly articles and books serve as sources to inform the methodology employed. This model is devised to enhance parental engagement in the educational journey, with a specific emphasis on fostering effective communication between teachers and parents. Through this collaborative effort, the aspiration is to cultivate a conducive learning environment conducive to the comprehensive development of students. This research delineates the process of crafting this framework and underscores the pivotal roles of educators and parents in augmenting children's academic performance in elementary education. Based on the findings gleaned from the aforementioned research, it can be inferred that the collaboration between teachers and parents is imperative to bolster the educational process and propel students towards achieving their highest academic potential.